FORMATION AND INSTALLATION OF RESTRICTIONS (ENCUMBRANCES) IN LAND USE - Dorosh, Y. M. (Землеустрій, кадастр і моніторинг земель, 2013)
The peculiarities of the formation and establishment of restrictions (encumbrances) of land use are elucidated. Concept of territorial restrictions (encumbrances) and re‐ strictions (encumbrances) in land plots use are differentiated.